Trend and Opportunity of Science Education Research Related Optical Waves: A Systematic Literature Network Analysis - Wahyudi Wahyudi; Agus Setiawan; Andi Suhandi (JIPF (Jurnal Ilmu Pendidikan Fisika), 2023)
Understanding the profile or trend of a research topic is very important and is the first step in starting research. The purpose of this study is to describe the profile of science education research related to wave optics learning. The systematic Literature Network Analysis (SLNA) method was used in this study. Article data during the last ten years (2012-2021) was collected from the Google Scholar database using the Publish or Perish (PoP) application. There were 109 eligible articles which were analyzed to find out research trends related to wave optics learning. The analysis results show that the number of studies and research citations has increased in the last ten years. The dominant waves optical materials studied are polarization and diffraction of light. This research is useful in finding further research opportunities related to wave optic learning. Further research related to the application of innovative media and inquiry learning strategies has the opportunity to be developed on wave optics (dispersion and interference). Further research can be focused on conceptual understanding and developing process skills and 21st-century skills for students through wave optics learning.